2012
DOI: 10.1016/j.drugalcdep.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil for the treatment of methamphetamine dependence

Abstract: Aim Modafinil was tested for efficacy in decreasing use in methamphetamine-dependent participants, compared to placebo. Methods This was a randomized, double-blind, placebo-controlled study, with 12 weeks of treatment and a 4-week follow-up. Eight outpatient substance abuse treatment clinics participated in the study. There were 210 treatment-seekers randomized, who all had a DSM-IV diagnosis of methamphetamine dependence; 68 participants to placebo, 72 to modafinil 200mg, and 70 to modafinil 400mg, taken on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 23 publications
2
87
1
1
Order By: Relevance
“…In contrast, several recent clinical trials failed to confirm the therapeutic efficacy of (±)-MOD in treatment of cocaine (Dackis et al, 2012) or methamphetamine dependence (Anderson et al, 2012;De La Garza et al, 2010;Lee et al, 2013). Similarly, conflicting results are reported for ( ± )-MOD as an adjunctive pharmacotherapeutic aid for smoking cessation.…”
Section: Introductionmentioning
confidence: 70%
“…In contrast, several recent clinical trials failed to confirm the therapeutic efficacy of (±)-MOD in treatment of cocaine (Dackis et al, 2012) or methamphetamine dependence (Anderson et al, 2012;De La Garza et al, 2010;Lee et al, 2013). Similarly, conflicting results are reported for ( ± )-MOD as an adjunctive pharmacotherapeutic aid for smoking cessation.…”
Section: Introductionmentioning
confidence: 70%
“…None showed clear efficacy for this indication. However, two of these studies (Shearer et al, 2009;Anderson et al, 2012) indicate through post hoc analyses that patients compliant with the medication do achieve better abstinence than noncompliant patients. Another study (Heinzerling et al, 2010) showed trends toward increased efficacy among users with high baseline methamphetamine use and low attendance in cognitive-behavioral therapy (although neither was statistically significant).…”
mentioning
confidence: 99%
“…There 40). There was no significant effect stratifying by intensity of methamphetamine use at baseline; effect of treatment over time had a p-value of 0.7 and 0.3 for light users and heavy users, respectively.…”
Section: Discussionmentioning
confidence: 99%